Analisis Patologi Sosial dalam Novel The Wind-Up Bird Chronicle Karya Haruki Murakami - Ajeng Cahyani; Nor Fatmah (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to identify and analyze forms of social pathology in Haruki Murakami’s The Wind-Up Bird Chronicle. Employing a qualitative content analysis approach, the research examines how historical violence and trauma, abuse of power, and existential alienation are represented through the novel’s narrative structure, characters, and symbolic elements. The findings indicate that these three categories are interconnected, forming a systemic pattern of social dysfunction rooted in institutional failure, historical memory, and individual psychological pressure. The depiction of war highlights collective trauma, while both physical and symbolic forms of domination illustrate distorted power relations. Furthermore, the motif of alienation reflects the psychological consequences of social instability and disrupted interpersonal bonds. The study aligns with previous research on trauma and deviance in Murakami’s works and strengthens the view of literature as a critical medium for reflecting modern social conditions.